PENETAPAN ITSBAT NIKAH DI PENGADILAN AGAMA DONGGALA KELAS I B - Haerani Husainy (Maleo Law Journal, 2019)
The research method uses empirical legal research, the writer conducts research directly to the location to obtain and collect data. Research carried out in the field is to examine problems that are qualitative. The results found that the Determination Form of a husband who has more than one wife (Itsbat Polygamy) is not acceptable as long as it is not in accordance with legal procedures, the application letter must be in the form of a controversial form, ie having the previous wife as the Respondent while the petition for the marriage is underage, the designation form was rejected. Must change application to Marriage Dispensation first. The research suggestion is that there should be a legal umbrella for the legal vacuum of itsbat marriage regarding the permissibility of itsbat marriage which occurs after the enactment of the Marriage Law, because of the increasing number of unregistered marriages which harms the wife and children born from underhand marriages Keyword: Determination, Itsbat Marriage